MANAJEMEN KESISWAAN DALAM MENGATASI PERILAKU BULLYING PADA PESERTA DIDIK DI SDN 115 PALEMBANG - Liyana, Tasya Arsy; Ahyani, Nur; Mahasir, Mahasir (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The success in organizing educational institutions cannot be separated from the influence of the management of the supporting components of educational activities, such as curriculum, students, financing, implementing personnel, and infrastructure This study aims to determine how student management in overcoming bullying behavior at SDN 115 Palembang. This research is a study that uses field research. The object of this research is student management and overcoming bullying behavior). Informants who can help in data collection are the principal, deputy head of student affairs, class teachers, and students at SDN 115 Palembang The results of this study were carried out by determining student management planning in overcoming bullying behavior and determining considerations before forming student management planning in overcoming bullying. The student management planning carried out is: 1) make a plan to implement counseling or socialization about bullying; 2) plan to approach students by establishing good communication and showing a high sense of caring for the school community; and 3) plan to make anti-bullying activities that can be done by making strict rules regarding bullying behavior.